“Familias disfuncionales y conducta de los estudiantes de educación general básica de la Unidad Educativa “Once de Noviembre”. Riobamba. Octubre 2017- Marzo 2018”. - Castañeda Velásquez, Tania Verónica (2018)
The present research project has the objective of determining the dysfunctional families and the behavior of the students of the Educational Unit "Once de Noviembre", because they are problems that need our greatest attention, theoretically we can mention that a dysfunctional family is a family in that the conflicts, the bad behavior, and often the abuse on the part of the individual members occurs continuously and regularly, the behavior is the set of acts, actions of the human being, methodologically our research is of a non-experimental design, of Bibliographical type, field and cross-sectional, with a descriptive, explanatory and correlational level, the population was 69 students of the fifth year of general basic education of the Educational Unit "Once de Noviembre", the techniques that were used was the BASC psychometric test, the structured history of the instrument and the S2 Questionnaire which helped us to collect data where it was possible to reach the conclusion that the relationship between dysfunctional families and behavior is evident given that the problems that exist between their parents affects the cognitive development of students.